2010
DOI: 10.4048/jbc.2010.13.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Patients with Triple-negative Breast Cancer and Brain Metastases

Abstract: Purpose: Patients with triple-negative breast cancer (TNBC) are known to carry an increased risk of distant metastasis and poor survival. The principal objective of this study was to investigate survival after brain metastases in patients with TNBC. Methods: The authors retrospectively evaluated clinical data obtained from 66 patients who had been diagnosed with breast cancer and brain metastasis from 2003 to 2009. Estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth receptor-2 (HER2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We initially evaluated the influence of biology from initial breast tumor over BM behavior and similarly to other publications we found that more advanced CS, ER-negative status, nonluminal and TN phenotypes were associated to shorter both TTCNS and survival after BM [1,2,4- 10,13]. These factors could predispose cancer cells not only to invade but also to grow inside brain tissue.…”
Section: Discussionmentioning
confidence: 85%
“…We initially evaluated the influence of biology from initial breast tumor over BM behavior and similarly to other publications we found that more advanced CS, ER-negative status, nonluminal and TN phenotypes were associated to shorter both TTCNS and survival after BM [1,2,4- 10,13]. These factors could predispose cancer cells not only to invade but also to grow inside brain tissue.…”
Section: Discussionmentioning
confidence: 85%
“…Negative HR status, nuclear grade 3, four or more positive lymph nodes and higher stage of the disease were factors considered to be associated with short time to BM in their series [31]. Kwon et al (2010) found that the time period from the initial BC to the onset of BM was 52.9, 33.6, and 25.5 months for patients with HR+, HER2+, and triple receptor negative tumors [32], which can probably be extrapolated in our study, because there is a link between the presence of these molecular markers and the evolution of BC in our patients. The prognostic factors involved in the development of BM originating in BC are tumor phenotype (HER2, ER status, HP grade, proliferative rate), the degree of the extension of the disease outside the brain (the presence of lung, bone and/or BMs), patient's age, as well as patient performance status [33,34].…”
Section:  Discussionmentioning
confidence: 96%